Self-Reported Visual Perceptual Abnormalities Are Strongly Associated with Core Clinical Features in Psychotic Disorders - Keane, Brian P.; Cruz, Lisa N.; Paterno, Danielle; Silverstein, Steven M. (Frontiers in Psychiatry, 2018)
Background Past studies using the Bonn Scale for the Assessment of Basic Symptoms (hereafter, Bonn Scale) have shown that self-reported perceptual/cognitive disturbances reveal which persons have or will soon develop schizophrenia. Here, we focused specifically on the clinical value of self-reported visual perceptual abnormalities (VPAs) since they are underexplored and have been associated with suicidal ideation, negative symptoms, and objective visual dysfunction. Method Using the 17 Bonn Scale vision items, we cross-sectionally investigated lifetime occurrence of VPAs in 21 first-episode psychosis and 22 chronic schizophrenia/schizoaffective disorder (SZ/SA) patients. Relationships were probed between VPAs and illness duration, symptom severity, current functioning, premorbid functioning, diagnosis, and age of onset. Results Increased VPAs were associated with: earlier age of onset; more delusions, hallucinations, bizarre behavior, and depressive symptoms; and worse premorbid social functioning, especially in the childhood and early adolescent phases. SZ/SA participants endorsed more VPAs as compared to those with schizophreniform or psychotic disorder-NOS, especially in the perception of color, bodies, faces, object movement, and double/reversed vision. The range of self-reported VPAs was strikingly similar between first-episode and chronic patients and did not depend on the type or amount of antipsychotic medication. As a comparative benchmark, lifetime occurrence of visual hallucinations did not depend on diagnosis and was linked only to poor premorbid social functioning. Conclusion A brief 17-item interview derived from the Bonn Scale is strongly associated with core clinical features in schizophrenia. VPAs hold promise for clarifying diagnosis, predicting outcome, and guiding neurocognitive investigations.